2012
DOI: 10.4103/2045-8932.97589
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Perspectives with Long‐Term Pulsed Inhaled Nitric Oxide for the Treatment of Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a chronic, progressive disease of the pulmonary vasculature with a high morbidity and mortality. Its pathobiology involves at least three interacting pathways – prostacyclin (PGI2), endothelin, and nitric oxide (NO). Current treatments target these three pathways utilizing PGI2 and its analogs, endothelin receptor antagonists, and phosphodiesterase type-5 (PDE-5) inhibitors. Inhaled nitric oxide (iNO) is approved for the treatment of hypoxic respiratory failure associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 69 publications
(197 reference statements)
0
28
1
Order By: Relevance
“…Nitric oxide readily crosses the alveolar-capillary membrane and quickly binds with hemoglobin, making it inactive, thus making it a selective pulmonary vasodilator. 25 Five potential issues with NO exist. First, NO has an extremely short half-life, a few seconds, requiring continuous administration of NO.…”
Section: Nitric Oxide Pathwaymentioning
confidence: 98%
See 2 more Smart Citations
“…Nitric oxide readily crosses the alveolar-capillary membrane and quickly binds with hemoglobin, making it inactive, thus making it a selective pulmonary vasodilator. 25 Five potential issues with NO exist. First, NO has an extremely short half-life, a few seconds, requiring continuous administration of NO.…”
Section: Nitric Oxide Pathwaymentioning
confidence: 98%
“…Second, patients on NO may cause increased levels of methemoglobin, but this is rarely an issue for patients receiving less than 100 ppm. 25 Third, NO may combine with oxygen to form nitrogen dioxide, a potentially toxic gas. 24 Care must be used to limit the time NO is exposed to oxygen, and nitrogen dioxide levels should be monitored, which is standard with the INOMax delivery system.…”
Section: Nitric Oxide Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently inhaled nitric oxide (iNO) has no role in the longterm management of PAH, having been assessed in pulsed nasal delivery and facemask form in small single-centre settings only [21,22].…”
Section: Inhaled Nitric Oxidementioning
confidence: 99%
“…The study suggested that 5–40 ppm of inhaled NO therapy may be appropriate and safe, while sustained treatment with 80 ppm NO increases the risk of adverse events. (77, 78)…”
Section: Inhaled Nitric Oxidementioning
confidence: 99%